Networks of Queues Models with Several Classes of Customers and Exponential Service Times - Ferreira, M. A. M. (arXiv:2110.08603, 2025)
The main target of this paper is to present the Markov chain C that, not giving explicitly the queue lengths stationary probabilities, has the necessary information to its determination for open networks of queues with several classes of customers and exponential service times, allowing to overcome ingeniously this problem. The situation for closed networks, in the same conditions, much easier is also presented.